Comprehensive assessment of patients with irritable bowel syndrome with constipation and chronic idiopathic constipation using deterministically linked administrative claims and patient-reported data: the Chronic Constipation and IBS-C Treatment and Outcomes Real-World Research Platform (CONTOR). (2nd October 2020) - Taylor, Douglas C. A.; Abel, Jessica L.; Martin, Carolyn; Doshi, Jalpa A.; Essoi, Breanna; Korrer, Stephanie; Reasner, David S.; Carson, Robyn T.; Hunter, Alyssa Goolsby
Abstract: Aims: To characterize a US population of patients with irritable bowel syndrome with constipation (IBS-C) or chronic idiopathic constipation (CIC) using CONTOR, a real-world longitudinal research platform that deterministically linked administrative claims data with patient-reported outcomes data among patients with these conditions. Methods: Patients with IBS-C or CIC were identified using diagnosis and treatment codes from administrative claims. Potential respondents received a mailed survey followed by 12 monthly online follow-up surveys and 2 mailed diaries. Surveys collected symptom severity, treatment use, quality of life, productivity, and condition/treatment history. Comorbidities and healthcare costs/utilization were captured from claims data. Diaries collected symptoms, treatments, and clinical outcomes at baseline and 12 months. Data were linked to create a patient-centric research platform. Results: Baseline surveys were returned by 2, 052 respondents (16.8% response rate) and retention rates throughout the study were high (64.8%–70.8%). Most participants reported burdensome symptoms despite having complex treatment histories that included multiple treatments over many years. More than half (55.3%) were dissatisfied with their treatment regimen; however, a higher proportion of those treated with prescription medications were satisfied. Limitations: The study sample may have been biased by patients with difficult-to-treat symptoms as a result of prior authorization processes for IBS-C/CIC prescriptions. Results may not be generalizable to uninsured or older populations because all participants had commercial insurance coverage. Conclusions: By combining administrative claims and patient-reported data over time, CONTOR afforded a deeper understanding of the IBS-C/CIC patient experience than could be achieved with 1 data source alone; for example, participants self-reported burdensome symptoms and treatment dissatisfaction despite making few treatment changes, highlighting an opportunity to improve patient management. This patient-centric approach to understanding real-world experience and management of a chronic condition could be leveraged for other conditions in which the patient experience is not adequately captured by standardized data sources.